Vitamin D deficiency in healthy children and associated factors (The Planet, 2024)
Introduction: This study aimed to investigate factors associated with vitamin D deficiency in healthy children in Bangladesh. This cross-sectional survey was conducted at the primary healthcare center from February 2021 to February 2022. The study included 200 healthy Bangladeshi nationals 5-16 years of age out of a random sample of 250 subjects approached, resulting in a response rate of 80%. Methods and Materials: Face-to-face interviews with a questionnaire were used to collect sociodemographic information, non-dietary covariates, dietary intake, vitamin D intake, type of feeding and laboratory investigations. These assessments cover various aspects of health status, including medical conditions, family history, body mass index, clinical manifestations, and biochemical parametes. Results: The study revealed a high prevalence of vitamin D deficiency in Bangladeshi adolescents (59.8% among 11-16 years old), followed by 5-10 year-olds (30.3%), and those aged < 5 years (9.9%). The likelihood of vitamin D deficiency increased with age, with a significant difference between the vitamin D-deficient and normal children. Additionally, vitamin D-deficient children had a lower average body mass index (17.9) than normal children (19.6). A family history of vitamin D deficiency was more common among children with vitamin D deficiency (68.9%) than among normal children (19.2%). Most children with vitamin D deficiency exhibit limited physical activity. The differences between the two groups were significant in terms of family history and physical activity. Low vitamin D levels are associated with reduced dietary and supplemental vitamin D intake. Vitamin D supplementation was lacking in both groups, with over half of the vitamin D-deficient (66.9%) and normal (51.9%) children not receiving any vitamin D supplements. Vitamin D-deficient children had poor dietary vitamin D intake, particularly from sources like vitamin D-fortified milk (64.9%) and fortified foods (26.4%). Conclusion: The study findings emphasize the high risk of vitamin D deficiency among Bangladeshi children. Key factors include limited outdoor activity, physical activity, and dietary vitamin D intake. Extended vitamin D supplementation is crucial to ensure the health and development of breastfeeding infants.
Keywords: Vitamin D deficiency; health children; vitamin D supplements